Strategies and Leadership in Improving The Quality of Islamic Education in Indonesia - Yasri Mandar; Yusron Hidayat; Fani Krismonadi; Ahwil Lutan Hidayah; Putri Nadha Setyaningrum; Sofwatun Nida (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
Islamic educational institutions still often face limited funds, minimal use of technology, and low managerial competence, which impacts the quality of learning.This research aims to improve the quality of education to realize the hope of Islamic education that has mental intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) for success in the world and the hereafter. The type of research used is qualitative with a library study approach, accompanied by primary sources in the form of educational books and secondary sources from several journal articles. The results of this study are strategies and leadership in improving the quality of Islamic education in Indonesia, emphasizing the importance of implementing planned strategies and competent leadership in the educational process. Improving the quality of Islamic education is not only related to the curriculum and teaching methods, but also includes developing teacher competence, utilizing technology, as well as community and government support. The quality of leadership, especially in understanding the principles of educational management, plays a very important role in maintaining and improving educational standards. Overall, improving the quality of Islamic education requires a synergy between careful planning, relevant strategies, insightful leadership, and the involvement of all stakeholders in the education system.